Pengaruh Budaya Organisasi, Kompetensi dan Motivasi Guru terhadap Kinerja Guru SMA Negeri Se-Kecamatan Samalanga Kabupaten Bireuen - Marzuki; Luthfi, Luthfi (Singkite Journal, 2023)
The research was conducted on 128 public high school teachers in Samalanga District, Bireuen Regency with the aim of knowing the effect of school organizational culture, teacher competency and teacher motivation on teacher performance. Data collection techniques through questionnaires and analysis methods with path analysis. With research results; 1. there is a direct effect of school organizational culture, and there is an indirect effect through teacher competence and teacher motivation on teacher performance of 16.63%. 2. There is a direct influence of teacher competence, or indirectly through school culture and teacher motivation factors on teacher performance of 40.18%. 3. There is a direct or indirect influence on teacher motivation through school organizational culture and teacher competence on teacher performance by 25.88%. And 4. Simultaneously the school organizational culture factors, teacher competence and teacher motivation, have a contribution of 82.90% to teacher performance.